Fostering Intrapreneurship, Creativity, and Innovation for Organizational Growth - Ni Putu Santinisah (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2025)
In an era marked by rapid technological disruption, shifting consumer expectations, and heightened global competition, organizational success increasingly hinges on the ability to adapt, innovate, and evolve from within. This research critically examines the synergistic relationship between intrapreneurship, creativity, and innovation as strategic pillars for driving sustainable organizational growth. This research outlines the mechanisms through which an intrapreneurial culture nurtures creative thinking and accelerates innovation cycles. It also examines critical success factors including leadership style, organizational structure, psychological safety, and performance incentives that enable or hinder these dynamics. This research is designed as an interpretive literature search. Data was collected through a structured literature review conducted on several leading academic databases. The research culminates in a set of practical recommendations for business leaders and policymakers seeking to institutionalize intrapreneurship and innovation at scale. By integrating these dimensions into core strategic planning, organizations can better position themselves to thrive in volatile and complex business landscapes.